Cat kid comic club collaborations - Pilkey , Dav; Pilkey , Dav; Pilkey , Dav (New York Graphix, an imprint of Scholastic, 2022)
"Excitement and imagination run wild as Naomi, Melvin, Poppy, Gilbert, Curly, and their siblings get back to making comics with originality and laughter. But wait--have they cleaned their rooms yet?! After their chores, the rambunctious group presents even more amazing mini-comics. By working together, the baby frogs discover that small things can have a huge impact."-- Provided by publisher
from the creator of dog man
Keywords: Comic strips